Organoruthenium Antagonists of Human A3 Adenosine Receptors. Issue 25 (23rd April 2013) - Paira, Priyankar; Chow, Mun Juinn; Venkatesan, Gopalakrishnan; Kosaraju, Vamsi Krishna; Cheong, Siew Lee; Klotz, Karl‐Norbert; Ang, Wee Han; Pastorin, Giorgia
Abstract Human A3 adenosine receptor (hA3AR) is a membrane‐bound G protein‐coupled receptor implicated in a number of severe pathological conditions, including cancer, in which it acts as a potential therapeutic target. To derive structure–activity relationships on pyrazolo–triazolo–pyrimidine (PTP)‐based A3AR antagonists, we developed a new class of organometallic inhibitors through replacement of the triazolo moiety with an organoruthenium fragment. The objective was to introduce by design structural diversity into the PTP scaffold in order to tune their binding efficacy toward the target receptor. These novel organoruthenium antagonists displayed good aquatic stability and moderate binding affinity toward the hA3 receptor in the low micromolar range. The assembly of these complexes through a template‐driven approach with selective ligand replacement at the metal center to control their steric and receptor‐binding properties is discussed.